Pattern and prevalence of vaping nicotine and non-nicotine drugs in the United Kingdom: a cross-sectional study. Issue 4 (26th April 2023) - Roberts, Emmert; Taylor, Eve; Cox, Sharon; Brose, Leonie; McNeill, Ann; Robson, Deborah
Abstract : Objectives: Electronic vaping devices are being used to consume nicotine and non-nicotine psychoactive drugs. We aimed to determine the pattern and prevalence of using vaping devices for nicotine and/or non-nicotine drug administration in the United Kingdom and how these differ by drug type and individual sociodemographic characteristics. We explored reasons for vaping onset and continuation. Design: An online cross-sectional survey Participants: A convenience sample of adults (aged ≥18 years) in the UK. Primary and secondary outcome measures: The primary outcome was prevalence of current use (within the last 30 days) of a vaping device to administer either nicotine or 18 types of non-nicotine drugs. We additionally evaluated reasons for onset and continuation of vaping. Sociodemographic characteristics were compared between the UK general population using census data and those vaping non-nicotine drugs. Results: We recruited 4027 participants of whom 1637 (40.7%) had ever used an electronic vaping device; 1495 (37.1%) had ever vaped nicotine and 593 (14.7%) had ever vaped a non-nicotine drug. Overall, 574 (14.3%) currently vaped nicotine and 74 (1.8%) currently vaped a non-nicotine drug. The most common currently vaped non-nicotine drug was cannabis (n=58, 1.4%). For nicotine, people's modal reasons to start and continue vaping was to quit smoking tobacco. For almost all other drugs, people's modal reason to start vaping was curiosity and to continue was enjoyment. Compared with the general population, the population who had ever vaped a non-nicotine drug were significantly younger, had more disabilities and fewer identified as white, female, heterosexual or religious. Conclusions: A non-trivial number of people report current use and ever use of an electronic vaping device for non-nicotine drug administration. As vaping technology advances and drug consumption changes, understanding patterns of use and associated behaviours are likely to be increasingly important to both users and healthcare professionals.